1958
DOI: 10.1121/1.1909563
|View full text |Cite
|
Sign up to set email alerts
|

Nasalization of Vowels in Relation to Nasals

Abstract: The principal characteristic features of nasalization of vowels are (1) a dull resonance around 250 cps, (2) an antiresonance at about 500 cps, (3) comparatively weak and diffuse components which fill the valleys between the formants. Features (1) and (3) are commonly found also during the period of oral closure of nasal constants, (3) in this case being influenced by the antiresonance of the oral cavity. The feature (3) affected by “antiformants” carries information about the tongue position du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
4

Year Published

1959
1959
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 0 publications
3
34
1
4
Order By: Relevance
“…• Extra poles and zeros in the spectrum: Several researchers in the past have reported the introduction of extra poles and zeros in the spectrum as the most important and con- 1960;Fujimura and Lindqvist, 1971;Hattori et al, 1958;Hawkins and Stevens, 1985;House and Stevens, 1956͒. Simulations in this study have shown that extra pole-zero pairs are introduced in the spectrum of a nasalized vowel because of ͑1͒ coupling between the vocal tract and the nasal tract, ͑2͒ asymmetry between the left and right passages of the nasal tract, and ͑3͒ the sinuses branching off from the nasal cavity walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Extra poles and zeros in the spectrum: Several researchers in the past have reported the introduction of extra poles and zeros in the spectrum as the most important and con- 1960;Fujimura and Lindqvist, 1971;Hattori et al, 1958;Hawkins and Stevens, 1985;House and Stevens, 1956͒. Simulations in this study have shown that extra pole-zero pairs are introduced in the spectrum of a nasalized vowel because of ͑1͒ coupling between the vocal tract and the nasal tract, ͑2͒ asymmetry between the left and right passages of the nasal tract, and ͑3͒ the sinuses branching off from the nasal cavity walls.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers have been successful in finding several acoustical ͑Bognar and Fujisaki, 1986;Dickson, 1962;Fant, 1960;Fujimura and Lindqvist, 1971;Hattori et al, 1958;Hawkins and Stevens, 1985;House and Stevens, 1956;Maeda, 1982b, c;Stevens et al, 1987͒ andperceptual ͑Beddor, 1993;Bognar and Fujisaki, 1986;Hattori et al, 1958;Hawkins and Stevens, 1985;House and Stevens, 1956;Maeda, 1982c͒ correlates of nasality, automatically extractable acoustic parameters ͑APs͒ that work well in a speaker-independent manner still remain elusive. A study to understand the salient features of nasalization, and the sources of acoustic variability in nasalized vowels is, therefore, not just desirable, but in fact needed to find knowledge-based APs to detect vowel nasalization.…”
Section: Introductionmentioning
confidence: 98%
“…͑2͒ Parameters that are related to the presence of a velopharyngeal opening in a vocalic region as in ͑1͒. These parameters include the amplitude of the F1 prominence in relation to the spectrum amplitude at low frequencies ͑200-300 Hz͒ and in the 1000-Hz range ͑Hattori et al., 1958;Chen, 1997͒. ͑3͒ Parameters that describe the spectrum change at times when there is rapid motion of articulators, particularly the lips and the tongue blade.…”
Section: Toward Estimation Of Acoustic Cues Relevant To Articulatomentioning
confidence: 99%
“…The path from the region of the velopharyngeal opening to the oral closure forms a side branch to the principal path -a side branch whose length depends on the place of articulation for the consonant. The distinguishing acoustic characteristics of nasal consonants during the closure interval is a low-frequency spectrum prominence (around 250 Hz) and a prominence in the vicinity of 900-1,000 Hz representing a resonance of the nasal cavity when the velopharyngeal port is open [13,14]. At the consonant-vowel boundary there is an abrupt change in the spectrum amplitude in the vicinity of the second formant, at a frequency that depends on the place of articulation of the consonant.…”
Section: Filtering With the Source At The Glottis: Non-mentioning
confidence: 99%